Seed dormancy and dormancy-breaking conditions of 12 West African woody species with high reforestation potential in the forest-savanna ecotone of Côte d’Ivoire - Koutouan-Kontchoi, Milène N.; Phartyal1, Shyam S.; Rosbakh, Sergey (Seed Science and Technology, 2020)
Information on the regeneration ecology of native woody species of the forest-savanna ecotone of West Africa is scarce, which is a major impediment to their optimal utilization in large-scale restoration programmes. The scattered information that is available for some of these species reveals that freshly matured seed are dormant. However, environmental heterogeneity among different habitats may results in inter-population seed dormancy variation. Thus, our objective was to re-examine the dormancy of 12 species from the forest-savanna ecotone that have been targeted for reforestation. Specifically, we aimed to examine the water-permeability of the seeds and explore the effectiveness of acid scarification and heat treatment to alleviate dormancy. Four species belonging to families other than Fabaceae and Malvaceae had water-permeable seeds. Two of them had nondormant (ND) seeds, and seeds of the other two species had a mixture of ND and other kinds of dormancy (possibly physiological dormancy, PD). Most species of Fabaceae and Malvaceae had water-impermeable seeds. All seeds of three species had physical dormant (PY), and some seeds of the remaining species had PY, while others were ND or had PD. Acid-scarification was effective in breaking PY and in augmenting imbibition and germination of non-PY seeds, while heat treatment was moderately effective in breaking dormancy. In general, acid scarification for 1-30 minutes and heat treatment for one hour at 55-75°C were optimal to enhance seed germination, depending on species. The present study has wide practical implications for park conservationists and restoration ecologists interested in producing bulk quantities of high-quality planting stocks of native woody species for large-scale restoration programmes.
Keywords: biodiversity conservation; climate mitigation; heat treatment; imbibition; native woody species; regeneration ecology; restoration; scarification; seed dormancy; Edouard K. Kouassi; Peter Poschlod; CCBAD